High employee involvement and well-being in the IT sector in the Republic of Serbia - Jevtić Tamara; Jevtić Jelena; Vidaković Mira (Ekonomija: teorija i praksa)
In the modern business environment, organizations are increasingly focusing on strategies and concepts that help them strengthen their competitive market position. This paper investigates human resource management models, with particular emphasis on high employee involvement and well-being. The aim of the research was to examine the relationship between these two factors. The theoretical part included a review of previous studies on high employee involvement and well-being, while the empirical research was conducted on a sample of 134 employees (managers and professionals) in IT sector organizations in the Republic of Serbia. Data was collected in January 2024 through an electronic questionnaire. The proposed relationship was tested using independent samples t-tests for high employee involvement and wellbeing by gender, as well as Spearman's correlation in IBM SPSS Statistics 25. The findings reveal a moderately strong positive correlation between high employee involvement and well-being. Employees involved in decision-making, problem-solving, and suggesting new ideas exhibited more developed mental, psychological, and emotional aspects of life.